2021
DOI: 10.1002/cam4.4016
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of TP73 profile prognostic significance in WHO grade II/III glioma

Abstract: Due to the extremely intrinsic heterogeneity among glioma patients, the outcomes of these patients are tremendously different. Therefore, the exploitation of novel biomarker classification of glioma is vitally important for deep insight into the essence and predicting the prognosis of glioma. We aim to analyze the correlation between TP73 mRNA expression, DNA methylated alteration and the prognosis of WHO grade II/III glioma, utilizing bioinformatics to evaluate its significance as a risk‐factor in predicting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Ribeiro showed that OSCC patients who had altered copy number of TP73 genes had a poor prognosis [ 31 ]. In gliomas, increased TP73 served as a stand-alone high-risk factor affecting the prognosis, while the downregulation of TP73 was closely related to favorable OS outcome [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ribeiro showed that OSCC patients who had altered copy number of TP73 genes had a poor prognosis [ 31 ]. In gliomas, increased TP73 served as a stand-alone high-risk factor affecting the prognosis, while the downregulation of TP73 was closely related to favorable OS outcome [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al confirmed that 8 methylation sites of TP73 gene CpG island were significantly positively associated with better OS and progression-free survival of patients diagnosed with grade II/III glioma. [ 41 ] EMILIN2 is an extracellular matrix protein, and LGG data from TCGA discovered that the EMILIN2 expression, negatively correlated to the EMILIN2 methylation, could predict a poor prognosis. [ 42 ] However, another research found that the inhibition of methylated miR-338-5p-5p in the promoter region was related to AOA invision.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA was synthesized with random priming and SuperScript™ IV reverse transcriptase (18090050, ThermoFisher, USA). The first PCR was performed as the previous report ( 17 ). The primers were specific for LHFPL3 and NTRK2 ( LHFPL3 -F: 5’-CTTCAAAGCCGCCTCCTTCTT, NTRK2 -R: 5’-TCCTGCTCAGGACAGAGGTTA).…”
Section: Methodsmentioning
confidence: 99%